The risk of toxoplasmic encephalitis in HIV-infected patients with different serological profiles of antitoxoplasma antibodies - Грижак, Ігор Гнатович (ScienceRise: Medical Science, 2016)
Aim of the work. To study the prevalence of serological signs of toxoplasmatic invasion among the HIV-positive population, structure and dynamics of antitoxoplasmatic antibodies and the risk of development of toxoplasmatic encephalitic. Methods of research. 926 HIV-positive persons were under three years observation: cohort of seropositives of toxoplasmosic included 531 persons and the cohort of seronegative ones – 395. Annually there were determined anti -Toxoplasma IgM, IgG and the frequency of toxoplasmosis of encephalitis in cohorts, the absolute and relative risk, the additional part of population risk were calculated. Results. The prevalence of seropositivity of toxoplasmosis in HIV-infected patients in Ivano-Frankivsk region is 57,25±1,6 %, that caused 86.84 % of additional part of population risk of toxoplasmatic encephalitis. The number of men (58,55 %) was more than the one of women (41,45 %). In seropositive cohort 4,16 % had toxoplasmatic encephalitis, that is 6 times more that in the cohort of seronegatives. The highest risk of morbidity was in the group of patients with seroreversion (21,43 %), that is 5 times more than in the whole cohort of seropositive persons (relative risk = 4,74) and 28 times more than in seronegative one (relative risk = 28.20). Seroreversion was also attended with the raised risk of toxoplasmatic encephalitis comparing with seronegative cohort (relative risk = 11,45). Conclusion: the highest risk of toxoplasmatic encephalitis was in patients with seroreversion of antibodies to toxoplasmas